Способ переработки гексафторида урана на металлический уран - Ремнев Г. Е. Геннадий Ефимович; Пушкарёв А. И. Александр Иванович; Пушкарёв М. И. Максим Иванович; Красильников В. А.; Гузеева Т. И. Татьяна Ивановна
опубл. 27.01.04